Lower Extremity Nerve Decompression for Diabetic Peripheral Neuropathy: A Systematic Review and Meta-analysis. Issue 8 (18th August 2022) - Fadel, Zahir T.; Imran, Wafa M.; Azhar, Turki
Abstract : Background: Diabetic peripheral neuropathy (DPN) is a leading cause of morbidity. This systematic review and meta-analysis evaluate the efficacy of lower extremity nerve decompression in reducing DPN symptoms and complications. Methods: A database search was performed using Medline, Embase, Google Scholar, and Cochrane Central Register of Controlled Trials. Articles addressing surgical decompression of lower limb peripheral nerves in patients with diabetes were screened for inclusion. Two independent reviewers undertook the assessment. Methodological quality measures were the Cochrane risk of bias and Newcastle-Ottawa scale. Results: The pooled sample size from 21 studies was 2169 patients. Meta-analysis of 16 observational studies showed significant improvement in the visual analog scale (VAS) ( P < 0.00001) and two-point discrimination ( P = 0.003), with strong reliability. Decompression of the tarsal tunnel region had the highest improvement in VAS [MD, 6.50 (95% CI, 3.56–9.44)]. A significant low-risk ratio (RR) of ulcer development and lower limb amputation was detected ( P < 0.00001). Lowest RR of ulcer development was detected with tarsal tunnel release [RR, 0.04 (95% CI, 0.00–0.48)]. Improvements in VAS, two-point discrimination, and nerve conduction velocity were nonsignificant in the meta-analysis of five randomized controlled trials (RCTs). The RCT analysis was limited to only two studies for each outcome. Conclusions: Meta-analysis of observational studies highlights the efficacy of lower extremity nerve decompression in reducing DPN symptoms, ulcerations, and amputations. Releasing the tibial nerve in the tarsal tunnel region was the most effective observed procedure. Nevertheless, high-quality RCTs are required to support the utility of this intervention in DPN.